2021
DOI: 10.5194/hess-25-1347-2021
|View full text |Cite
|
Sign up to set email alerts
|

Do small and large floods have the same drivers of change? A regional attribution analysis in Europe

Abstract: Abstract. Recent studies have shown evidence of increasing and decreasing trends for average floods and flood quantiles across Europe. Studies attributing observed changes in flood peaks to their drivers have mostly focused on the average flood behaviour, without distinguishing small and large floods. This paper proposes a new framework for attributing flood changes to potential drivers, as a function of return period (T), in a regional context. We assume flood peaks to follow a non-stationary regional Gumbel … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 54 publications
6
40
0
Order By: Relevance
“…Another promising research line is the attempt to detect and attribute changes that differentiates between small and large floods. Bertola et al (2020Bertola et al ( , 2021 showed that the 100-year flood changed differently than the 2-year flood in some European regions and that these changes can be attributed to different drivers. Similarly, recent studies have shown that small and large floods respond differently to changes in precipitation (Brunner et al, 2021;Wasko et al, 2019Wasko et al, , 2021.…”
Section: Clarifying the Effects Of Temporal Changes On Upper Flood Tailsmentioning
confidence: 99%
“…Another promising research line is the attempt to detect and attribute changes that differentiates between small and large floods. Bertola et al (2020Bertola et al ( , 2021 showed that the 100-year flood changed differently than the 2-year flood in some European regions and that these changes can be attributed to different drivers. Similarly, recent studies have shown that small and large floods respond differently to changes in precipitation (Brunner et al, 2021;Wasko et al, 2019Wasko et al, , 2021.…”
Section: Clarifying the Effects Of Temporal Changes On Upper Flood Tailsmentioning
confidence: 99%
“…7 in Wasko and Nathan, 2019). In temperate climates of northwestern Europe, extreme precipitation is an important flood driver, while in the drier climates of southern Europe, both antecedent soil moisture and extreme precipitation matter (with a greater importance of soil moisture for smaller floods; Bertola et al, 2021). Increases in precipitation intensity are more likely to cause increases in streamflow in smaller catchments (Wasko and Sharma, 2017;Wasko and Nathan, 2019).…”
Section: Climate Variability and Changementioning
confidence: 99%
“…Numerous studies showed that arterial and field drainage can affect flood peaks (increasing magnitude and reducing time to peak; e.g. Wilcock and Wilcock, 1995;Bhattarai and O'Connor, 2004). Conversely, our understanding of the impacts of drainage on low flows and drought remains poor, as does our understanding of how other components of runoff response are affected due to inadequate monitoring of subsurface hydrological processes.…”
Section: Water Resources Management and Geomorphological Changementioning
confidence: 99%
“…For example, by using circular statistics analysis, Berghuijs et al (2019) examined the relative importance of three flooding mechanisms based on the seasonality of floods and three potential drivers such as the largest daily precipitation, the largest daily soil moisture excess, and the largest daily snowmelt. Bertola et al (2021) attributed changes in the magnitude of flood quantiles to changes in possible drivers by using regression analysis and determined their contributions to flood changes accordingly. In contrast to these analyses conducted at catchment or coarser levels, Kemter et al (2020) and Stein et al (2020) performed event-based classifications to determine flooding mechanisms in respective regions or catchments, both using manual criteria but with different indicators and thresholds.…”
Section: Comparative Analysis With Other Studiesmentioning
confidence: 99%
“…In recent years, numerous studies have investigated river flooding mechanisms and some of them have provided Europeanscale assessments (e.g., Berghuijs et al, 2016;Berghuijs et al, 2019;Kemter et al, 2020;Bertola et al, 2021;Stein et al, 2021). Catchment-level floods can typically be attributed to the interaction of hydro-meteorological processes, such as extreme precipitation, soil moisture excess, and snowmelt (Merz and Blöschl, 2003;Tarasova et al, 2019).…”
mentioning
confidence: 99%